2000
DOI: 10.1111/j.1572-0241.2000.03297.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum Leptin Levels in Patients With Nonalcoholic Steatohepatitis

Abstract: The serum leptin levels were significantly higher in patients with NASH, while they were not affected by chronic hepatitis. This elevation is out of proportion to BMI of these patients and may be related to hyperlipidemia in most. Elevated serum leptin levels, therefore, may promote hepatic steatosis and steatohepatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
48
1
7

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(63 citation statements)
references
References 21 publications
7
48
1
7
Order By: Relevance
“…Subjects with HS (particularly grades II-III) have higher leptin concentrations (Figure 2). This result is similar to other reports [28] , however it is not observed in all series. Hui et al [24] , found this pattern only in men, but other reports do not agree with this finding [29] .…”
Section: Discussionsupporting
confidence: 82%
“…Subjects with HS (particularly grades II-III) have higher leptin concentrations (Figure 2). This result is similar to other reports [28] , however it is not observed in all series. Hui et al [24] , found this pattern only in men, but other reports do not agree with this finding [29] .…”
Section: Discussionsupporting
confidence: 82%
“…Also, low amounts of leptin has been shown to be secreted by other tissues, such as placenta, skeletal muscles, stomach fundus and culture-activated hepatic stellate cells[108]. Leptin plays the role of a peptide hormone, regulating food uptake and energy consumption of the body through central feedback mechanisms and relating eating to hypothalamus and adipose tissue mass ( i.e ., it controls food uptake and increases energy consumption)[102,108,109]. The importance of this regulatory role is such that recombinant leptin has been studied for treatment of all prevalent types of obesity in different clinical trials[110-113].…”
Section: Inflammatory Markersmentioning
confidence: 99%
“…It has been shown that increased serum leptin level in patients with steatohepatitis has no relation with BMI of these patients, and this increase could not be easily justified by the patient’s sex, obesity or type 2 diabetes[109,114]. In contrast, another study indicated a correlation between human serum level of leptin and body fat percent and BMI[115].…”
Section: Inflammatory Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…Among all of these cytokines, IL-6 is both proinflammatory and a useful marker for obesity-associated inflammation. In the liver, IL-6 is mainly secreted by KC and hepatic stellate cells (HSC) and to a lesser extent by stimulated hepatocytes [86, 87]. Earlier studies have also revealed that both IL-6 and TNF increase hepatic production of C-reactive protein (CRP), a major acute phase protein, which is a nonspecific but sensitive marker of infection and tissue inflammation that is increased in obesity [8890].…”
Section: The Common Causes Of Genetic Alterations and Genomic Instmentioning
confidence: 99%